Les transformateurs Lyotard: L'intellectuel et l'art des métamorphoses - Géorges van den Abbeele (Carnets)
Throughout his career as a philosopher, Jean-François Lyotard continually asks the question of what an "intellectual" is for our times. For Lyotard, the role of the intellectual as the spokesperson for an extended community (nation, proletariat, common people) is no longer possible. Taking stock of the metamorphoses of the figure of the intellectual, including the intellectual metamorphoses of Lyotard himself from a certain Marxism and Freudianism toward a "philosophy of phrases," I propose an analysis of his key book, Les TRANSformateurs DUchamp, as a pivotal work between his "libidinal" philosophy" of the 1970s and the ulterior development of an ethical pragmatics of philosophy and art which guides Lyotard's work in the 1980s and 90s.